(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
The present study aims to evaluate the effect of essential oil (EO) from Cymbopogon citratus leaves against the spoilage flora of fresh orange juice. Thus, the EO was extracted by hydrodistillation from fresh leaves of Cymbopogon citratus collected in southern Benin and its chemical composition was determined by gas chromatography, coupled to mass spectrometry (GC/MS). Orange samples were collected from large production areas of South and Central Benin and juices were extracted by mechanical pressing. After identification of spoilage flora of fresh orange juice, antimicrobial tests were carried out with the EO of Cymbopogon citratus to evaluate its antimicrobial activity on spoilage flora of fresh orange juice. Results indicate that the spoilage flora of fresh orange juice is mainly composed of fungi belonging to the genera of Cladosporium, Penicillium and Fusarium. Bacteria such as Enterobacter cloacae and Enterobacter aerogenes were also identified in some samples. The major compounds identified in the EO by GC/MS are Neral (33.0%) and geranial (41.3%) with a predominance of oxygenated monoterpenes (85.5%). Antimicrobial tests have revealed a high antibacterial activity of the EO, with minimum bactericidal concentrations (MBC) between 0.1 and 0.15 μL.mL-1. Antifungal tests revealed that fungi are also susceptible to this EO with minimum fungicidal concentration (MFC) between 0.15 and 0.25 μL.mL-1. Results obtained during the evaluation of the physicochemical characteristics of the orange juice stored by adding EO, indicated a significant decrease in the pH and vitamin C content. However, with EO concentration of 0.250 μL.mL-1, the pH of stored juice was 6.4 ± 0.1 after 15 days of preservation, with a best vitamin C content of 28.06 ± 0.03 mg / 100mL. The EO of Cymbopogon citratus, with high antimicrobial activity, could be used as an alternative in the preservation of fruit juices, replacing antimicrobials from chemical synthesis.